1959
DOI: 10.1104/pp.34.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Auxin-membrane Permeability Relations in Fruit and Leaf Tissues

Abstract: In a previous paper (22)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1960
1960
1994
1994

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 13 publications
(11 reference statements)
1
20
0
Order By: Relevance
“…It was probably related to the clogging of the air spaces by the cell exudate. Sacher (18) reported extensive liquid logging in senescent cells of bean endocarp and some fruits.…”
Section: Resultsmentioning
confidence: 99%
“…It was probably related to the clogging of the air spaces by the cell exudate. Sacher (18) reported extensive liquid logging in senescent cells of bean endocarp and some fruits.…”
Section: Resultsmentioning
confidence: 99%
“…root, and leaf is that the TPNH/TPN ratio in every organ decreases accompanying that organ's senescence. The effect of in(loleacetic acid in (lelaying senescence has often been reported (21). According to Marre aind Bianchetti (17), the value of the TPNH/TPN ratio is increased by indoleacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Some reports have indicated that auxins may also be able to delay senescence. For example, a-naphthalene acetic acid retards the senescence of Rhoeo and Mesetnhryanthemum leaf segments (Sacher, 1959) and 2,4-D butyl ester slows down protein breakdown of detached leaves of Prunus serrulata (Osborne & Hallaway, 1964). However, there are numerous cases in which auxins are not very powerful in their effects on senescence, and high concentrations have to be used compared with cytokinins.…”
Section: Plant Grozcth Regulators (A) Cytokininsmentioning
confidence: 99%